EFEKTIVITAS MODEL ENVIRONMENTAL LEARNING DALAM PEMBELAJARAN MENULIS KREATIF MAHASISWA PBSI - Fransisca Despa Listiani; Pranowo Pranowo; R Kunjana Rahardi; Yuliana Setyaningsih (Kajian Linguistik dan Sastra, 2021)
Abstrak This article aims to describe the steps of implementing environmental learning models in learning creative writing fable material and describing its effectiveness. This research is a type of research mix research using a mixture of quantitative and qualitative methods. Data collection techniques using observation methods, questionnaires, and tests. Through research can be known measures implementing environmental learning model in learning creative writing fable material include: (1) environmental exploration, (2) reporting on the results of environmental exploration, (3) determining themes, figures, background, moral messages, and other elements of builders, (4) making the framework according to structure, (5) developing the skeleton into the text fable, (6) editing fable text, and (7) publication of fable. Fable text analysis and test results show that the fable text written by a student group using environmental learning models has good quality in terms of content, organization, vocabulary, linguistic, and writing. The average group of students who use environmental learning models in writing fable 85.58, while the group of students using conventional models is 76.52. It provides ample evidence that an effective environmental learning model is used in learning to write fable rather than conventional models that are commonly performed.